(untitled) (Jurnal Adabiya, 2021)
The effects of internet use bring with it many negative aspects linked to online fake news in Indonesia. Indonesia’s fight against the spread of online fake news has been going on for many years. However, in 2017, the country experienced the biggest challenges in the bid to battle and resolve the rise of post-truth politics in the country. In addition, the spread of fake news in Islam is prohibited and perspectives from Islamic law equally discouraged the same. There is no harm in making gossip focused on sharing real experiences and emotions but Islam forbids any information being made with the intention of spreading rumors or falsehood. Therefore, the aim of this paper is to discuss online fake news based on Indonesia Law and Islamic Perfectives. The study conducts descriptive analytical literature review methods without using a basic assumption or proposition. Also, the literature used by the author for data collection includes primary and secondary sources from previous studies, such as publications, reference books, online news verification; and ayahs from Qur’an & Hadith that are centered on Indonesia Cyber Crime Law Settings. Cybercriminal offense governed in Law No. 11 Year 2008 on Information and Electronic Transactions (UUITE) relating to online fake news item number one: criminal offenses involved in illegal activities, such as: distribution or propagation, transmission, unavailability of illegal content, including: ethics (Article 27[1] UUITE), gambling (Article 27 [2] UUITE); disrespect or defamation (Article 27 [3] UUITE); outrage or threats (Article 27 [4] UUITE), hoax manipulating and damaging customers (Article 28 [1] UUITE); creates a sense of ethnic hostility-based bigotry (Article 28 [2] UUITE). Equally, online fake news is also not allowed in Islam and that is evident in some ayahs stated in the Qur’an, which among are: Qur’an (49:6) & (24:15). Since online fake news has to do with spreading lie, falsehood, rumors and gossips, Islam condemns all kinds of deceit. Therefore, spreading rumors should not be treated as trivial or casual nor be encouraged as a form entertainment due to the high concerns it can raise and its far-reaching implications.